Designing a system for Online Orchestra: Peripheral equipment. Issue 2 (1st December 2017) - Prior, David; Reeder, Philip; Rofe, Michael; Biscoe, Ian; Murray, Samuel
Online Orchestra is a telematic performance project, aimed at enabling young and amateur musicians in geographically remote locations to make music together over the Internet. This article reports the processes by which the audio and video peripheral equipment used for Online Orchestra was chosen and how the system was designed and used. Starting with an overview of guiding design principles, a description of methods for choosing, integrating and configuring audio and video hardware is presented. Following the development of the project from initial workgroups to the pilot performance of Online Orchestra, this article compares the 'ideal' test scenarios of workgroups with the reality of deploying the technology in a performance context and concludes with an account of using the system on site.